SMEs, success, and capital startups: Evidence from the service sector in South Africa - Ogujiuba Kanayo; Ebenezer Gbenga Olamide; Estelle Boshoff; Isaac Agholor; Chinelo Ogujiuba (Administrative Sciences, 2023)
Financing has been identified as a major stumbling block to the effective launch and long-term success of SMEs, particularly in emerging economies. However, little is known about the impact of capital startups on SMEs' performance in South Africa. Thus, the aim of this article is to compare differences in business success for three different levels of Capital startups and to determine the impact of capital startups on SMEs' performance. The analysis was premised on a two-tail hypothesis test that the average weights of the three groups are different. The Cronbach Alpha test and the test-re-test reliability approach on the survey instrument indicated values of 0.70 and 0.875, respectively. A one-way between-groups analysis of variance was conducted startup. There was a statistically significant difference at the p < 0.05 level in scores for the three groups (F (2, 477) = 12.967 p = 0.0000). Post hoc comparisons using the Tukey HSD test indicated that the mean scores for Group 1 (M = 19.93, SD = 6.343) were significantly different from Group 2 (M = 20.94, SD = 2.309) and Group 3 (M = 21.73, SD = 2.880). Despite reaching statistical significance, the actual difference in mean scores between the groups was quite small. The one-way ANOVA approach indicates that finance (startup capital) remains a significant impediment to the effective launch of service-providing SMEs. It is recommended that SMEs who want to raise startup capital must create a solid business plan or build a prototype to sell the idea. This will assist them in discussions with venture capitalists, angel investors, banks, or other financial institutions.
Keywords: 350; business; capital; entrepreneurship; finance; service; South Africa